Karakteristik Guru dalam Tradisi Pendidikan Nahdlatul Wathan, Lombok - Prosmala Hadisaputra; Ahmad bin Yussuf; Tengku Sarina Aini Binti Tengku Kasim (At-Tafkir, 2020)
This article discusses the characteristics of teacher who teaches Islamic sciences in the perspective of the Nahdlatul Wathan educational tradition, comprehensively. On the other hand, this article is one form of response to the moral degradation of teachers that have recently been rife, especially in Indonesia. This article is the result of qualitative research with a literature approach. Primary data are the books of Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid (Sheikh), which include Wasiat Renungan Masa (Book), Batu Ngompal (Book), the struggle song of Nahdlatul Wathan, and the recording of Sheikh's speech during his lifetime. Secondary data consists of scientific journals and relevant research results, as well as Islamic education books, Sufism, tafsīr and hadīth. Data was collected offline and online, then analyzed by using the NVivo 12 Plus software. This study shows that nine characteristics must be possessed by religious teachers who teach in the Nahdlatul Wathan madrasas/pesantrean (Islamic boarding school), namely: murshīd, sincere, obedient, mandate, behave as the teacher's morals, have a clear pedigree (silsilah/sanad), wise and polite in speaking, competent, and straight (istiqamah). This study concludes that the characteristics of the teacher mentioned in the will of the Sheikh are based on the results of contemplation (tafakkur), empirical experience (tajrībah), and extensive knowledge.